2011
DOI: 10.1007/978-3-642-22263-4_1
|View full text |Cite
|
Sign up to set email alerts
|

How Unique and Traceable Are Usernames?

Abstract: International audienceSuppose you find the same username on different online services, what is the probability that these usernames refer to the same physical person? This work addresses what appears to be a fairly simple question, which has many implications for anonymity and privacy on the Internet. One possible way of estimating this probability would be to look at the public information associated to the two accounts and try to match them. However, for most services, these information are chosen by the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(130 citation statements)
references
References 17 publications
(18 reference statements)
1
129
0
Order By: Relevance
“…Regarding issues to users' anonymity, a recent study has demonstrated that pseudonyms chosen by users at different websites can be linked to deduce their real identity [28]. This probability of linking and profiling users could increase if users' pseudonyms can be identified based on their lock pattern behavior when authenticating into different services.…”
Section: Related Workmentioning
confidence: 99%
“…Regarding issues to users' anonymity, a recent study has demonstrated that pseudonyms chosen by users at different websites can be linked to deduce their real identity [28]. This probability of linking and profiling users could increase if users' pseudonyms can be identified based on their lock pattern behavior when authenticating into different services.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, as the user ID is unique, it can be used to track a user across different apps. Finally, there is substantial evidence that user ID (and username) can be used to (re)identify a user [8]. We observe that 1% of apps are transmitting age to an external entity; this attribute is considered highly sensitive and only few users disclose it publicly [3].…”
Section: Data Leakage Classificationmentioning
confidence: 90%
“…Zafarani et al [20] explored how the behavior features of how users express themselves and generate their usernames. Perito et al [16] studied username choice discloses our identities to public, while Liu et al [12] improves name disambiguation by modeling the commonality of usernames, to help better estimate the linkage likelihood.…”
Section: Identifying Users Across Social Networkmentioning
confidence: 99%